Perilaku Konsumen dalam Pembelian Kopi di Coffe Shop - Edy Humaidi; Analianasari Analianasari; Bina Unteawati (Fakultas Pertanian, Universitas Timor, 2023)
The purpose of this study was to analyze the factors that influence the purchasing decisions of coffee consumers at the coffee shop, to analyze the factors that influence consumer behavior in buying coffee at the coffee shop. This research was conducted using a survey method. The sampling method in this study was carried out using the Non-Probability Sampling method, namely convenience sampling. The analysis technique used is quantitative descriptive analysis using PLS Structural Equation Modeling (SEM). The results of the analysis show that of the five variables namely atmosphere, price, service quality, product quality, and environment, only the price variable influences the decision to buy coffee in a coffee shop with P-values of 0.013 (<0.05). Among the three variables, namely service quality, customer satisfaction and product quality, only customer satisfaction has an effect on consumer loyalty, with P-values of 0.000 (<0.05). Meanwhile, only the service quality variable has a significant effect on customer satisfaction with a P-value of 0.000 (<0.05).